ANALISIS GAYA KEPEMIMPINAN LURAH DALAM MENINGKATKAN KINERJA PEGAWAI PADA KELURAHAN MARTUBUNG - Sinatra, Franciscus Tuah Xaverius; Muda, Indra (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the leadership style applied in Martubung Village, Medan Labuhan District. This study uses a descriptive approach with qualitative methods. Research informants include village officials and residents of Sidorejo Village. Data were obtained through in-depth interviews, direct observation, and related documentation. Data analysis techniques were carried out using an interactive approach, which includes data reduction, data presentation, and drawing conclusions. Based on the results of the research presented and developed, the Leadership Style of Martubung Village includes a delegative leadership style, which is able to delegate work and be given authority according to their main duties and functions. The more participatory leadership style of Martubung Village makes employees feel happy for better employee performance, one of which shows that Martubung Village uses a participatory leadership style, namely discussions, exchanging ideas and meetings held before activities, it can be concluded that the leadership style of Martubung Village is reflected in its behavior in leading daily government at the Village Office. This leadership style encourages village employees to carry out their responsibilities as public servants better. These positive conditions are created through cooperation between the village head and village officials, with the aim of achieving organizational targets that have been set based on applicable laws and government regulations.